Ovarian Tumor Domain-Containing Proteases-Deubiquitylation Enzyme Gene SsCI33130 Involved in the Regulation of Mating/Filamentation and Pathogenicity in Sporisorium scitamineum - Li, Huizhong; Cai, Yichang; Deng, Quanqing; Bao, Han; Chen, Jianwen; Shen, Wankuan (Frontiers in Microbiology, 2021)
Sugarcane is an important sugar crop. Sugarcane smut, caused by Sporisorium scitamineum, is a sugarcane disease that causes serious economic losses worldwide, yet no effective control measures exist. Developing effective prevention and control technology for evaluating the pathogenic mechanism of S. scitamineum at the molecular level is thus warranted. Deubiquitinase (DUB) removes ubiquitin molecules from their binding substrates and participates in a variety of physiological activities in eukaryotes. Based on the transcriptome sequencing data of two isolates (Ss16 and Ss47) of S.scitamineum with different pathogenicities, SsCI33130, a gene encoding an OTU1-deubiquitin enzyme, was identified. The positive knockout mutants and complementary mutants of the SsCI33130 gene were successfully obtained by polyethylene glycol-mediated protoplast transformation technology. Phenotypic comparison of the growth, morphology, abiotic stress, sexual mating, pathogenicity, and gene expression levels of the knockout mutants, complementary mutants, and their wild-type strains were conducted. The results showed that the gene had almost no effect on abiotic stress, cell wall integrity, growth, and morphology, but was related to the sexual mating and pathogenicity of S. scitamineum. The sexual mating ability and pathogenicity between the knockout mutants or between the knockout mutant and wild-type were more significantly reduced than between the wild-types, the complementary mutants, or the wild-types and complementary mutants. The sexual mating between the knockout mutants or between the knockout mutant and wild-type could be restored by the exogenous addition of small-molecule signaling substances such as 5 mM cyclic adenosine monophosphate (cAMP) or 0.02 mM tryptophol. In addition, during sexual mating, the expression levels of tryptophol and cAMP synthesis-related genes between the knockout mutants were significantly lower than those between the wild-types, while the expression levels between the complementary mutants were restored to the level of the wild-type. It is speculated that the SsCI33130 gene may be involved in the development of sexual mating and pathogenicity in S. scitamineum by regulating the synthesis of the small-molecule signaling substances (cAMP or tryptophol) required during the sexual mating of S. scitamineum, thereby providing a molecular basis for the study of the pathogenic mechanisms of S. scitamineum.